1986
DOI: 10.1161/01.str.17.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nimodipine on acute focal cerebral ischemia.

Abstract: SUMMARY Nimodipine is a calcium slow channel blocker with several pharmacologlc properties suggesting the potential to favorably modify outcome in focal cerebral ischemia. Thirty adult cats underwent unilateral middle cerebral artery (MCA) occlusion for 4 hours. Seventeen cats were treated with an ipsilateral intracarotid infusion of nimodipine (1 /xg kg" 1 min ~') beginning 15 minutes before MCA ocdusion and continuing throughout the occlusion period. Eight nimodipine treated cats maintaining MAP > 90 mmHg we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Indeed, in experiments involving ligation of a cerebral artery (Steen et al, 1983;Smith et al, 1983;Mohamed et al, 1985;Newberg Milde et al, 1986) or experimental subarachnoid haemorrhage (McCalden et al, 1986) impairment of cerebral blood flow, due to an increase in vasomotor tone in the post-ischaemic or post-haemorrhagic phase, can be alleviated by nimodipine. However, negative reports have also been published (Barnett et al, 1986;Schuier & Ulrich, 1987;Sahlin et al, 1987;Berger & Hakim, 1988). From the present and other studies the question arises whether the differences in results can be explained by differences in preparations only (conscious versus anaesthetized, open versus closed skull) or that differences in species may be the dominant factor.…”
Section: Cerebral Bloodflowmentioning
confidence: 62%
“…Indeed, in experiments involving ligation of a cerebral artery (Steen et al, 1983;Smith et al, 1983;Mohamed et al, 1985;Newberg Milde et al, 1986) or experimental subarachnoid haemorrhage (McCalden et al, 1986) impairment of cerebral blood flow, due to an increase in vasomotor tone in the post-ischaemic or post-haemorrhagic phase, can be alleviated by nimodipine. However, negative reports have also been published (Barnett et al, 1986;Schuier & Ulrich, 1987;Sahlin et al, 1987;Berger & Hakim, 1988). From the present and other studies the question arises whether the differences in results can be explained by differences in preparations only (conscious versus anaesthetized, open versus closed skull) or that differences in species may be the dominant factor.…”
Section: Cerebral Bloodflowmentioning
confidence: 62%
“…It has been reported that mild hypotension induced by phlebotomy (MAP < 90 mm Hg) negates the beneficial effects of nimodipine on EEG recovery and reperfusion (colloidal carbon filling) following regional cerebral ischemia in cats. 4 Thus, we cannot exclude the possibility that differences in MAP between groups may have affected neurologic outcome. The effects of NE and TMP on postischemic brain are not known with certainty.…”
Section: Discussionmentioning
confidence: 98%
“…- 22 In our study we limited the recirculation period after ischemia to 3 hours. Within that period an evident improvement with nimodipine treatment was found in the morphologic appearance of CA, neurons in the hippocampus; EEG activity after ischemia returned significantly sooner and the appearance of final recordings after 2 hours of recirculation was much better than in control rabbits.…”
Section: Discussionmentioning
confidence: 99%